Graphene-based hybrid nanoparticle of doxorubicin for cancer chemotherapy - SreeHarsha N (Dove Medical Press, 2019)
Nagaraja SreeHarsha,1 Rahul Maheshwari,2,3 Bandar E Al-Dhubiab,1 Muktika Tekade,4 Mukesh Chandra Sharma,4 Katharigatta N Venugopala,1,5 Rakesh Kumar Tekade,2,6–7 Abdullah M Alzahrani8 1Department of Pharmaceutical Sciences, College of Clinical Pharmacy, King Faisal University, Al-Ahsa, Saudi Arabia; 2National Institute of Pharmaceutical Education and Research (NIPER) – Ahmedabad, Gandhinagar, Gujarat 382355, India; 3School of Pharmacy and Technology Management, SVKM’s NMIMS, Hyderabad Campus, Hyderabad, Telangana 509 301, India; 4School of Pharmacy, Devi Ahilya Vishwavidyalaya, Takshila Campus, Indore, MP 452001, India; 5Department of Biotechnology and Food Technology, Durban University of Technology, Durban 4001, South Africa; 6Department of Pharmaceutical Technology, The International Medical University, School of Pharmacy, Kuala Lumpur 57000, Malaysia; 7Department of Materials Engineering, Indian Institute of Technology-Jammu, Jammu - 181 221, J&K, India; 8Department of Biological Sciences, College of Science, King Faisal University, Al-Ahsa, Saudi ArabiaCorrespondence: Nagaraja SreeHarshaDepartment of Pharmaceutical Sciences, College of Clinical Pharmacy, King Faisal University, PO Box 380, Al-Ahsa 31982, Saudi ArabiaEmail sharsha@kfu.edu.saBackground: Prostate cancer (PC) has the highest prevalence in men and accounts for a high rate of neoplasia-related death. Doxorubicin (DOX) is one of the most widely used anti-neoplastic drugs for prostate cancer among others. However, it has low specificity and many side effects and affects normal cells. More recently, there have been newly developed drug delivery tools which are graphene or graphene-based, used to increase the specificity of the delivered drug molecules. The graphene derivatives possess both π-π stacking and increased hydrophobicity, factors that increase the likelihood of drug delivery. Despite this, the hydrophilicity of graphene remains problematic, as it induced problems with stability. For this reason, the use of a chitosan coating remains one way to modify the surface features of graphene.Method: In this investigation, a hybrid nanoparticle that consisted of a DOX-loaded reduced graphene oxide that is stabilized with chitosan (rGOD-HNP) was developed.Result: The newly developed rGOD-HNP demonstrated high biocompatibility and efficiency in entrapping DOX (∼65%) and releasing it in a controlled manner (∼50% release in 48 h). Furthermore, it was also demonstrated that rGOD-HNP can intracellularly deliver DOX and more specifically in PC-3 prostate cancer cells.Conclusion: This delivery tool offers a feasible and viable method to deliver DOX photo-thermally in the treatment of prostate cancer.Keywords: graphene, photothermal, chitosan, hybrid nanoparticles, HNP, prostate cancer